La conjura revolucionaria del 14 de abril / José-Oriol Cuffí Canadell, Pablo López Castellote ; prólogo del... Conde de Salces de Ebro - López i Castellote, Pau (1929-1994) Salces de Ebro, Eduardo Conde Garriga, Conde de (1899-1975); Cuffí Canadell, José-Oriol?
Fecha tomada de fuente externa